Higher Education Finance in Ghana - Atuahene, Francis (International Higher Education, 2008)
The diminishing financial resources and the growing demand for participation remain the biggest threat to higher education in Ghana. Cognizant of these quagmires and realizing the impact of higher education on national development, the National Union of Ghanaian Students proposed and the government established a special education trust fund called the Ghana Education Trust Fund bill (GETFund) in 2000. Despite these challenges, the GETFund is making significant contributions toward higher education development in Ghana in infrastructure, student development, faculty research, and staff support.